UK national and regional trends in cardiovascular magnetic resonance usage – the British Society of CMR survey results. (25th November 2020) - Keenan, N; Captur, G; McCann, G; Berry, C; Myerson, S; Fairbairn, T; Hudsmith, L; O'Regan, D; Westwood, M; Greenwood, J
Abstract: Background: CMR is an imaging modality recommended for multiple indications. Access to CMR is a key issue for its clinical use. We surveyed all CMR units in the UK. Methods: An online survey of CMR units in the UK, with responses analysed by region and compared with population data. Results: Response rate was 100% (Table). The UK performed a total of 102, 886 scans in 2017, and 117, 967 in 2018 representing a 1-year 14.7% increase and a 10-year increase of 573% compared to 2008 data (20, 597).By head of population in 2018 there were 1, 776 CMR scans per million people, with significant variation nationally and regionally, e.g. 4, 256 per million in London vs. 396 per million in Wales (Figure). Mean number of scans per unit was 1, 404, (range 98–10, 000) with wide variation in referral to diagnostic times (mean 45.7 days, range 5–180) (Figure). Clinical indications for CMR were: heart failure 21%, cardiomyopathy 27%, function and viability 22%, stress 24%, vascular disease 5%, valvular 5%, myocarditis/pericardial 10%, paediatric /congenital 10%, others e.g. transplant/masses 4%, with overlap. There were 358 consultants reporting CMR in 2018 (234 (65%) cardiologists and 124 (35%) radiologists). 81% of units had a CMR service for patients with pacemakers and defibrillators. Conclusion: The survey shows the state of CMR in the UK. The 10-year growth has been remarkable, but there are wide disparities in terms of use, access and wait times with potential implications for clinical care. Action is needed to make access equitable across the UK. Funding Acknowledgement: Type of funding source: None